Graphothek - Birnie Danzker, Jo-Anne; Ott-Osterwold, Gabriele; London Regional Art and Historical Museums, London, Ontario; Maison de la Culture Plateau Mont-Royal, Montréal; Mendel Art Gallery, Saskatoon (Vancouver : Goethe-Institut, 1990)
ABR ; Atkinson, Terry ; Aycock, Alice ; Baselitz, Georg ; Blume, Bernhard Johannes ; Boltanski, Christian ; Bunk, Holger ; Buthe, Michael ; Christian, Abraham David ; Clegg & Guttmann ; Colette ; Dahn, Walter ; etc.
Graphothek, Goethe-Institut, Vancouver, British Columbia, September 18 - October 19, 1990 ; London Regional Art and Historical Museums, London, Ontario, November 24, 1990 - January 13, 1991 ; Maison de la Culture Plateau Mont-Royal, Montréal, Québec, 29 Janvier - 24 Février, 1991 ; Mendel Art Gallery, Saskatoon, Saskatchewan, April 19 - June 2, 1991
Duits & Engels & Frans
kunstcatalogus